Anforderungen der Ingenieurwissenschaften an das Forschungsdatenmanagement der Universität Stuttgart - Ergebnisse der Bedarfsanalyse des Projektes DIPL-ING - Iglezakis, Dorothea; Schembera, Björn (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2018)
The importance of research data as the basis of all scientific reasoning is not always reflected in their management. Particularly in the engineering disciplines there is a backlog demand in research data management to make data reusable, reproducible and verifiable. The following publication summarizes the outcomes of the requirement analysis conducted for the project DIPL-ING. This project aims to deliver concepts for data management in infrastructures, processes and life cycles in engineering. By means of concrete use cases from the fields of technical thermodynamics and aerodynamics, problems and requirements of engineering disciplines were identified and addressed. Specific requirements result from the fact that the research in these fields is mainly based on software and code which produce huge amounts of raw and analyzed data. To facilitate reasonable reuse, either internally or externally, discipline-specific metadata standards are needed to document the provenance of data and codes and ensure the retrieval as well as the comprehensibility of the data. In addition, there is a lack of discipline-specific guidelines recommending which part of the data should be archived and for what period of time. The publication of data requires infrastructures that can handle large volumes of data as well as software code and provide quality and access control.